Crossfit training in the process of preparation of the motorized athletes - Byzdra, Krzysztof; Szturmowski, Mateusz; Stępniak, Robert (Journal of Education, Health and Sport, 2017)
The work describes the impact of crossfit training on the level of motor skills of athletes, practicing individual and team disciplines. In the first chapter, I analyzed the progress of each component of human efficiency. I presented how you can use them in your sport. The next chapter contains a description of the use of specific crossfit training exercises in the process of motor preparation of athletes and their impact on the achieved sports results. Also i have included a chapter on the possibilities of self-accelerating regeneration after training and optimization of the biomechanical conditions of the athlete's body, which gives mobility training. The third chapter contains information about programming and periodisation of trainings, taking into account the individual needs of the athlete and the part of the season in which I am currently. The applications are full of concise information about the benefits of this training, but also about the possible dangers of its practice.